2011
DOI: 10.1002/anie.201103151
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalyzed Enantioselective Fluorocyclizations

Abstract: Enantioenriched fluorinated heterocycles can be prepared through fluorocyclizations of prochiral indoles (see scheme; Ts=tosyl, Bn=benzyl, Boc=tert-butoxycarbonyl). More than twenty examples for this cascade fluorination-cyclization, which is catalyzed by cinchona alkaloids and employs N-fluorobenzenesulfonimide as the electrophilic fluorine source have been explored, and an unprecedented catalytic asymmetric difluorocyclization has also been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
87
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(89 citation statements)
references
References 51 publications
0
87
0
2
Order By: Relevance
“…60 Various tryptamine derivatives underwent electrophilic fluorination/cyclization using N -fluorobenzenesulfonamide (NFSI) in the presence of 20 mol% of Sharpless’s (DHQ) 2 PHAL ligand (Scheme 36). Conditions using a stoichiometric amount of chiral ligand gave enantioselectivities up to 90% (not shown).…”
Section: Catalytic Enantioselective Alkene Aminohalogenationsmentioning
confidence: 99%
“…60 Various tryptamine derivatives underwent electrophilic fluorination/cyclization using N -fluorobenzenesulfonamide (NFSI) in the presence of 20 mol% of Sharpless’s (DHQ) 2 PHAL ligand (Scheme 36). Conditions using a stoichiometric amount of chiral ligand gave enantioselectivities up to 90% (not shown).…”
Section: Catalytic Enantioselective Alkene Aminohalogenationsmentioning
confidence: 99%
“…59 (8) The first enantioselective intramolecular aminofluorination was reported by Gouverneur and co-workers in 2011. 60 Various tryptamine derivatives underwent electrophilic fluorination/ cyclization using N-fluorobenzenesulfonamide (NFSI) in the presence of 20 mol% of Sharpless's (DHQ) 2 PHAL ligand (Scheme 36). Conditions using a stoichiometric amount of chiral ligand gave enantioselectivities up to 90% (not shown).…”
Section: Intramolecular Enantioselective Organocatalytic Aminohalogenmentioning
confidence: 99%
“…While electrophilic fluorination of olefins with oxygen nucleophiles has been wellprecedented, [8,9] reports using nitrogen nucleophiles have been rare. [10][11][12] Previous examples of enantioselective aminofluorination reactions of isolated olefins have been disclosed, but to the best of our knowledge the analogous transformation utilizing 1,3-dienes is unknown. Herein we report the first catalytic asymmetric 1,4-aminofluorination of conjugated dienes using chiral-anion phase-transfer catalysis.…”
mentioning
confidence: 98%
“…By lowering the stoichiometry of the base in the reaction, the enantioselectivity could be further improved to 89 % ee with full conversion of the starting material in fluorobenzene (entry 10). Subsequent solvent and concentration screening revealed that a,a,a-trifluorotoluene (PhCF 3 ) was the ideal solvent for the transformation (entries [11][12][13][14], affording 2 a in 96 % ee with complete conversion of the starting material (entry 13).…”
mentioning
confidence: 99%